'They simply do not understand': a focus group study exploring the lived experiences of family caregivers of people with frontotemporal dementia. (1st February 2022) - Bruinsma, Jeroen; Peetoom, Kirsten; Bakker, Christian; Boots, Lizzy; Verhey, Frans; de Vugt, Marjolein
Abstract: Background: Frontotemporal dementia (FTD) has a profound impact on the spouse and other family caregivers involved. While caregivers have a need for support, it is difficult for healthcare providers to respond to their specific needs. This qualitative study explores the lived experiences and needs of caregivers of persons with FTD to facilitate the development of support. Methods: Three focus group discussions were organized to explore the lived experiences of Dutch FTD caregivers. The included caregivers ( n = 24) were aged 16 years or older and were involved in the care of a relative with FTD. Two researchers independently performed an inductive content analysis using open and axial coding. Results: The main category emerging from the data was a lack of recognition, acknowledgment, and understanding experienced by caregivers. This was linked to caregivers' experiences with (1) complex emotional and behavioral symptoms in the person with FTD, (2) the trivializing responses of family and friends, (3) a perceived lack of knowledge and support from healthcare professionals, and (4) the bureaucratic procedures that accompany caregiving. As a result, caregivers felt lonely and solely responsible for the caregiving role. Conclusion: Caregivers of persons with FTD experience a lack of understanding in caring for their relative with FTD, which contributes to feelings of loneliness. A specialized support approach is needed to address the specific needs of caregivers of persons with FTD. Support should address strategies that caregivers can use to inform and involve family and friends in the caregiving situation to prevent loneliness in FTD caregivers.